Method for isolation of pancreatic blood vessels, their culture and coculture with islets of langerhans. (6th December 2018) - Lehmann, Vivian; Andersen, Parker L.; Damodaran, Rajesh G.; Vermette, Patrick
Abstract : The only cure available for Type 1 diabetes involves the transplantation of islets of Langerhans isolated from donor organs. However, success rates are relatively low. Disconnection from vasculature upon isolation and insufficient rate of revascularization upon transplantation are thought to be a major cause, as islet survival and function depend on extensive vascularization. Research has thus turned toward the development of pretransplantation culture techniques to enhance revascularization of islets, so far with limited success. With the aim to develop a technique to enhance islet revascularization, this work proposes a method to isolate and culture pancreas‐derived blood vessels. Using a mild multistep digestion method, pancreatic blood vessels were retrieved from whole murine pancreata and cultured in collagen Type 1. After 8 days, 50% of tissue explants had formed anastomosed microvessels which extended up to 300 μm from the explant tissue and expressed endothelial cell marker CD31 but not ductal marker CK19. Cocultures with islets of Langerhans revealed survival of both tissues and insulin expression by islets up to 8 days post‐embedding. Microvessels were frequently found to encapsulate islets, however no islet penetration could be detected. This study reports for the first time the isolation and culture of pancreatic blood vessels. The methods and results presented in this work provide a novel explant culture model for angiogenesis and tissue engineering research with relevance to islet biology. It opens the door for in vivo validation of the potential of these pancreatic blood vessel explants to improve islet transplantation therapies . © 2018 American Institute of Chemical Engineers Biotechnol. Prog ., 35: e2745, 2019.